Relevansi Standarisasi Pembelajaran Dan Penilaian Pada Kurikulum 2013 Dengan Konsep Perbedaan Individu Peserta Didik - Novan Ardy Wiyani (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2017)
Abstract: This paper examines the relevance of standardization in the process of learning and assessment to the curriculum 2013 with the concept of individual differences in learners. It then raises two questions. First, whether the learning and assessment is in the standard curriculum. Second, can the learning and assessment is in a standardized curriculum perspective when faced with the concept of individual differences in learners. Discussion of the results showed that the learning and assessment in the perspective of standards curriculum or have standards. But when confronted with the concept of individual differences in learners, learning and assessment less suitable to be standardized. It should be a paradigm shift in the organization of learning, the learning paradigm based on the standard into the learning paradigm based on individual differences. Keywords: learning, assessment, standards, learners.